Woman's role as owner/manager in the framework of Albanian business - Shyqyri Llaci; Vasilika Kume (Journal for East European Management Studies, 1997)
Even in the current civilized society, the women have not yet taken heir deserved place. Despite the obvious difficulties in Albania, as well as in the rest of the world, the number of female owners is increasing every day. As their businesses are new, most of them are in the introductory phase of their existance (survival, consolidation and control). Women as managers are facing several problems related to the lack of resources and inadequate knowledge and skills in management. The difficulties are increased by the fact that they are women. However, based upon the analysis of the characteristics of a strategic model of management in business owned by woman, we can state that the behaviour of female entrepreneurs is equal to that of male counterparts, but with some characteristics in the management style. – – Auch in der heutigen 'zivilisierten' Gesellschaft hat die Frau noch immer nicht den Platz eingenommen den sie verdient. Ungeachtet der offensichtlichen Schwierigkeiten in Albanien, wie auch im Rest der Welt, steigt die Zahl weiblicher Firmeneigentümer täglich. Die Mehrheit von ihnen befindet sich aber noch in der Anfangsphase ihrer wirtschaftlichen Existenz. Manager sehen sich einer Reihe von Problemen wie Ressourcenknappheit oder einem Mangel an Wissen und Fähigkeiten auf dem Gebiet des Managements gegenüber. Diese Schwierigkeiten treffen weibliche Manager in besonderem Maße.
Keywords: 650